Comparison of Mid-Upper-Arm Circumference and Weight-For-Height Z-Score in Identifying Severe Acute Malnutrition among Children Aged 6–59 Months in South Gondar Zone, Ethiopia - Dereje Birhanu Abitew; Alemayehu Worku Yalew; Afework Mulugeta Bezabih; Alessandra N. Bazzano (Journal of Nutrition and Metabolism)
Children with severe acute malnutrition (SAM) are identified for admission to outpatient therapeutic programs using mid-upper-arm circumference (MUAC) or weight for height (WHZ). However, MUAC and WHZ do not identify the same children, and such observed differences might have programmatic implications of missed nutrition therapy if only MUAC is used to identify children with SAM. The objective of the study was to assess any difference in prevalence and degree of agreement between MUAC and WHZ in identifying SAM affected children. A cross-sectional study was conducted in South Gondar Zone, Ethiopia, among 17 districts, with 3 districts and 10 health centers with their clustered health posts selected randomly. A total of 2,040 children were recruited, and data were collected using a parent questionnaire then entered into EpiData and analyzed using SPSS v 20. A total of 1,980 respondents (97.1%) were interviewed, all of whom were female and rural residents. Children’s mean age in months was 23.2 (SD ± 9.7), and 54% were male children. The prevalence of SAM based on MUAC <11.5 cm was 11.2% (95% CI: 9.9–12.7) and 11.0% (95% CI: 9.7–12.5) based on WHZ <−3. The agreement between MUAC and WHZ was good (k = 0.729). The proportion of children with SAM identified using both MUAC and WHZ was 61.2%. The prevalence of SAM identified using both MUAC and WHZ was comparable. A substantial degree of agreement between MUAC and WHZ was observed to diagnose SAM. Therefore, MUAC can be used as an appropriate tool in identifying children with SAM for admission into the outpatient therapeutic program (OTP) in the study area.